Realisasi Progresif Implementasi Program Jaminan Kesehatan Nasional dan Kartu Indonesia Sehat - Brian Azeri; Wahyu Pratama Tamba; Raja Andreas Silaban (Pancasila: Jurnal Keindonesiaan, 2025)
The right to health is a human right that must be progressively realized through welfare state policies. The 5th Precept of Pancasila affirms the state's commitment to ensure social justice, including inclusive access to health services. This study analyzes the implementation of the National Health Insurance Program (JKN) and the Healthy Indonesia Card (KIS) with a qualitative approach through literature studies and secondary data analysis. The main data sources refer to reference books and various research journals. The results of the analysis show that despite the significant increase in coverage from 52% in 2014 to 94.6% in 2023 and the increase in participant satisfaction, there are still issues of inequality, especially for vulnerable groups. This study identifies the main problems of the JKN-KIS program as gaps in service quality, equity of access, and financial sustainability of the program. The research is expected to provide conceptual contributions regarding good practices and challenges in implementing universal health coverage through the JKN-KIS program based on the values of human rights and Pancasila.